The management of acne vulgaris in young people in primary care: A retrospective cohort study - Moosa, Aminath Shiwaza; Lim, Shu Fen; Koh, Yi Ling Eileen; Aau, Wai Keong; Tan, Ngiap Chuan (Frontiers in Medicine, 2023)
Background: Acne vulgaris (acne) is common among young persons (YPs). Clinical practice guidelines are available for acne management to minimize their physical and psychological impact. However, evidence of adherence to these guidelines is sparse in primary care practices. The study aimed to determine the demographic profile of YPs who sought primary care consultations for acne, their related prescriptions and referrals to specialists for further management. Method: A retrospective study was conducted using data from a cluster of eight public primary care clinics in Singapore. Demographic, clinical, prescription and referral data were extracted from the electronic health records of YPs aged 10-29 years with a documented diagnosis of acne (ICD-10 classification) from 1st July 2018 to 30th June 2020. The data were reviewed, audited for eligibility criteria and de-identified before analysis. Results: Complete data from 2700 YPs with acne were analyzed. Male (56.1%) YPs and those of Chinese ethnicity (73.8%) had the most frequent attendances for acne. The mean and median age at presentation was 19.2 (standard deviation=4.3) and 19 (interquartile range=16-22) years, respectively. Only 69.7% of YPs received an acne-related medication; 33.5% received antibiotic monotherapy; 53.0% were prescribed oral doxycycline, 35.0% acne cream (combination of sulfur, salicylic acid, and resorcinol), 28.4% benzoyl peroxide 5% gel; 54.3% of those treated with antibiotics were prescribed with a shorter duration than recommended; 51.3% were referred to a dermatologist on their first visit, and 15.8% had more than one visit. Conclusion: Acne management for YPs can be enhanced with refresher training among primary care physicians for better adherence to its clinical practice guidelines.